Kinerja Pelayanan Perusahaan Daerah Air Minum ( PDAM) Di Kabupaten Gowa - Hamia, Hamia; Mahsyar, Abdul; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2021)
This study aimed to analyze and describe the service performance of regional water companies (PDAMs) in Gowa Regency. The research method wad descriptive qualitative. The number of informants in the study were 7 people. Data collection techniques were observation, interview and documentation . Data analysis used data reduction, data presentation and conclusion. The results of this study showed that the service performance of regional water supply companies (PDAMs) in Gowa Regency, the service performance of the Tierta Jeneberang Regional Water Supply Company in terms of quality had been run well and the services that had carried out in accordance with the operational standards of service, although there were still complaints about the quality of water distributed to the customers. While, in terms of productivity had been done to the maximum, various community complaints had addressed one by one. However, the community was not satisfied with the performance of PDAM Tirta Jeneberang, Gowa Regency, which had to be more responsive with the complaints from the community so that the community was satisfied with the services provided.